2021
DOI: 10.3389/fmicb.2021.742114
|View full text |Cite
|
Sign up to set email alerts
|

Hfq Regulates Efflux Pump Expression and Purine Metabolic Pathway to Increase Trimethoprim Resistance in Aeromonas veronii

Abstract: Aeromonas veronii (A. veronii) is a zoonotic pathogen. It causes clinically a variety of diseases such as dysentery, bacteremia, and meningitis, and brings huge losses to aquaculture. A. veronii has been documented as a multiple antibiotic resistant bacterium. Hfq (host factor for RNA bacteriophage Qβ replication) participates in the regulations of the virulence, adhesion, and nitrogen fixation, effecting on the growth, metabolism synthesis and stress resistance in bacteria. The deletion of hfq gene in A. vero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Previous studies reported that Gram-negative bacteria, E. coli or Aeromonas veronii , devoid of Hfq are more sensitive to antibiotics [ 36 , 37 ]. Furthermore, deleting the hfq gene results in an increase in antibiotic accumulation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies reported that Gram-negative bacteria, E. coli or Aeromonas veronii , devoid of Hfq are more sensitive to antibiotics [ 36 , 37 ]. Furthermore, deleting the hfq gene results in an increase in antibiotic accumulation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This pump is composed of three proteins: AcrB is an active drug transporter that functions with the proton-motive force across the IM; TolC forms an OM channel; and AcrA is a periplasmic linker [ 33 , 34 , 35 ]. Two studies have shown that Hfq plays a role in regulating acrB expression, and therefore, Hfq may contribute to antibiotic resistance [ 36 , 37 ]. Furthermore, Hfq modulates antibiotic import.…”
Section: Introductionmentioning
confidence: 99%